Evolution of technology and technology governance - Richard Almgren; Dmitry Skobelev (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study is based on the concept of Kondratiev's technological waves as an analytical instrument for examining the processes of technological evolution. It aims at setting feasible indicators for this evolutionary development in order to provide a regulatory instrument for policy makers. In order to do so, the authors analyze approaches used for resource efficiency improvement in several European countries (i.e., implementation of Best Available Techniques, BAT). They emphasize that in Russia, the BAT concept is seen primarily as an industrial policy instrument. While BAT-based legislation is enforced by the environmental authorities, technological innovations making it possible to achieve performance better than that required by BAT are supported by the industrial development authorities. In the conclusions, the authors state that BAT-based solutions could be used as drivers for developing and implementing new technological solutions (innovations) and should become the basis for working out state industrial and environmental policies. The results of policies currently being developed will be assessed by the end of 2024.
Keywords: 650; innovation; Best Available Techniques; environmental policy; evolution of technology; industrial modernization; industrial strategy; resource efficiency; technological waves; technology governance